Meta-analysis of the effects of dietary sugar on intake and productivity of dairy cattle - Vargas, C. F.; Reinhardt, Christopher D.; Firkins, J. L.; Bradford, Barry J. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2014)
A meta-analysis was performed to determine the possible effects of dietary sugar on feed intake and milk production in lactating dairy cattle. The database used in this analysis included 18 treatment comparisons frozm 10 studies reported from 1985 through 2011. Treatment comparisons were used only if: (1) either sucrose (9 comparisons) or molasses (9 comparisons) replaced corn grain without adding fat; and (2) sugar added by treatment ranged from 2 to 5% of dry matter. First, responses to sucrose and molasses were compared to assess whether these sugar sources could be considered together. Statistical analysis provided no evidence for different responses across sugar sources for dry matter intake (DMI), milk yield, energy-corrected milk (ECM) yield, milk fat content, or milk protein content. Different sugar sources were pooled for the remaining analyses; the combined data showed that adding sugar tended to increase DMI by 0.84 lb/day and milk fat content by 0.085%. No effects were detected for milk yield, ECM yield, or milk protein content. This analysis indicates that adding 2 to 5% dietary sugar may promote small increases in DMI and milk fat content but does not consistently increase ECM yield in lactating dairy cattle.
Dairy Research, 2012 is known as Dairy Day, 2012
Keywords: Molasses; Sucrose; Lactation; Dry matter intake (DMI); Dairy cattle